Quantum probability communications - Attal, Stéphane (World Scientific, 2003)
Integral-sum kernel operators / J. Martin Lindsay -- Quantum probability applied to the damped harmonic oscillator / Hans Maassen -- Quantum probability and strong quantum Markov processes / K.R. Parthasarathy -- Limit problems for quantum dynamical semigroups -- inspired by scattering theory / Rolando Rebolledo -- A survey of operator algebras / Jean-Luc Sauvageot -- Quantum stop times / Kalyan B. Sinha -- Free calculus / Roland Speicher -- Continuous kernel processes in quantum probability / Wilhelm von Waldenfels.
Includes bibliographical references. - Description based on print version record
Keywords: Electronic books